AB0708 INFLUENCE OF IMMUNOGENICITY ON LONG-TERM MAINTENANCE OF ADALIMUMAB IN SPONDYLOARTHRITIS. (June 2019) - Samain, Marine; Ducourau, Emilie; Rispens, Theo; Dernis, Emmanuelle; Guilchard, Fabienne Le; Andras, Lucia; Perdriger, Aleth; Lespessailles, Eric; Martin, Antoine; Cormier, Grégoire; Armingeat, Thomas; Devauchelle-Pensec, Valerie; et al.
Abstract : Background: Immunogenicity of anti TNF monoclonal antibodies leads to poor or secondary loss of response. Methotrexate reduces anti-drug antibodies (ADA) to adalimumab at week 26 in spondyloarthritis (SpA). 1 Objectives: Herein we sought to examine adalimumab long term persistence in aDA positive versus aDA negative SpA patients. Methods: The CoMARIS study (Combination of Methotrexate and adalimumab to Reduce Immunization in patients with axial SpA) is a 26-week prospective, randomised, open-labelled, multicentre study in which patients received adalimumab 40 mg subcutaneously (s.c.) every other week either in combination with MTX 10 mg s.c. For 26 weeks or without MTX. In a post hoc analysis, we reviewed the charts of patients to assess adalimumab persistence. A Cox model analysis was performed to test the following covariates: MTX combination or not, sex, presence of aDA at week 26. Results: Data from 104 patients (54 without MTX and 50 with MTX) were reviewed, and time of adalimumab discontinuation was collected. The median time of follow-up was 210.57 weeks. ADA positivity at week 26 was the only covariate associated with adalimumab persistence. The median retention rate of adalimumab in aDA positive patients was 56.9 weeks, as compared with 98.6 weeks in those without aDA (log rank: p=0.015). In the Cox model analysis, the presence of aDA at week 26 increased the risk of adalimumab discontinuation by 1.78 [IC 95%=1.11-2.85], p=0.016. Conclusion: Immunogenicity is a key factor that contributes to adalimumab discontinuation in SpA. MTX at initiation may therefore be considered in combination to adalimumab in SpA patients. References: [1] Ducourau E, et al. Methotrexate reduces adalimumab immunogenicity in patients with spondyloarthritis: a randomized clinical trial. EULAR17-1527. Acknowledgement: This work was promoted by the Regional University Hospital Center of Tours and supported by grants from the French Ministry for Health and Sport within the framework of the Programme Hospitalier de Recherche Clinique 2011. Disclosure of interests: Marine Samain: None declared, Emilie Ducourau Speakers bureau: BMS and abbvie, theo Rispens Grant/research support from: Genmab, Speakers bureau: Pfizer, abbvie, Regeneron, Emmanuelle Dernis: None declared, Fabienne Le Guilchard: None declared, Lucia andras: None declared, aleth Perdriger: None declared, Eric Lespessailles Grant/research support from: Grants/research support from amgen, Eli Lily, MSD, UCB., Consultant for: Consultant for amgen, Expanscience, Eli Lilly, MSD, UCB., antoine Martin: None declared, Grégoire Cormier: None declared, Thomas armingeat: None declared, Valerie Devauchelle-Pensec Grant/research support from: Roche-Chugai, Speakers bureau: MSD, BMS, UCB, Roche, Elisabeth Gervais Speakers bureau: abbvie, BMS, MSD, Pﬁzer, Roche, UCB, Novartis, Benoit Le Goff Speakers bureau: abbvie, BMS, Janssen, MSD, Pﬁzer, Sanoﬁ-Genzyme, UCB, Novartis, annick de Vries: None declared, Eric Piver: None declared, Gilles Paintaud Grant/research support from: Novartis, Roche Pharma, Sanofi-Genzyme, Chugai, Pfizer and Shire, Céline Desvignes: None declared, David Ternant Speakers bureau: Sanofi, amgen, Hervé Watier: None declared, Philippe Goupille Grant/research support from: Financial compensation received from MSD on a pro-rota basis for participation in Scientific Committee meetings and functions for this study, Speakers bureau: abbvie, Biogaran, BMS, Hospira, Janssen, MSD, Pﬁzer, Sanoﬁ-Genzyme, UCB, Denis Mulleman Speakers bureau: Pfizer, Novartis, Grifols